Facile and Environmentally Friendly Synthesis of Low-defect Few-Layers Graphene (FLG) Using Combined Shear Exfoliation Methods - Amri, Amun; Wulandari, Revika; Fabryza, Dhina; Sunarno, Sunarno; Heltina, Desi; Bahri, Syaiful; Sarma, Deki; Miran, Hussein A.; Rahman, M. Mahbubur; Altarawneh, Mohammednoor; Jiang, Zhong Tao (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
This study presents an environmentally friendly and scalable method for synthesizing high-quality few-layer graphene (FLG) through a combination of turbulence-assisted shear exfoliation (TASE) and high shear exfoliation (HSE) techniques. By systematically varying the high-shear mixer (HSM) speed (3000–5000 rpm) and processing time (1–3 hours), we precisely controlled key material attributes, including the number of graphene layers, crystallinity, lateral size, and defect density. Optimal conditions (5000 rpm, 3 hours) resulted in FLG with 2–3 layers, confirmed by a symmetric 2D peak with a full-width at half-maximum (FWHM) of 35 cm⁻¹ and a high I2D/IG ratio ( 0.6), indicating excellent structural integrity. The ID/IG ratio ( 0.1) further verified the presence of minimal defects, predominantly edge vacancies rather than oxidative disruptions. Raman imaging revealed a dominance of zigzag edge chirality, while TEM and PSA analyses demonstrated control over lateral size ( 396.5 nm) and particle uniformity. The application of household dishwashing liquid as a green surfactant innovatively enabled selective and pure exfoliation. This work highlights how precise modulation of shear parameters can directly influence graphene quality, paving the way for sustainable large-scale production of low-defect FLG.